Ekokiritik Sastra Dalam Buku Anak-Anak Seribu Sungai Jilid 1-5 Karya Rahman Hafiz Al Mubaraq - Putri Apridah; Noor Indah Wulandari (JURNAL MANAJEMEN PENDIDIKAN, 2026)
LITERARY ECOCRITICS IN THE CHILDREN'S BOOK A THOUSAND RIVERS VOLUME 1-5 BY RAHMAN HAFIZ AL MUBARAQ Children's literature plays a strategic role in building ecological awareness from an early age. Rahman Hafiz Al Mubaraq's book "Stories for Children of a Thousand Rivers" volumes 1–5 presents a depiction of the life of river communities who are closely connected to nature and their surroundings. This representation is interesting to study because it contains ecological values ​​that are relevant to current environmental conditions. This study aims to describe the depiction of nature and analyze the relationship between humans and nature reflected in the book "Stories for Children of a Thousand Rivers" volumes 1–5 based on a study of literary ecocriticism. This study uses a qualitative approach with a descriptive method. The research data source is the book "Stories for Children of a Thousand Rivers" volumes 1–5 by Rahman Hafiz Al Mubaraq. The research data consists of story excerpts containing depictions of nature and the relationship between humans and nature. Data collection techniques are carried out through reading and note-taking techniques. Data analysis techniques are carried out through the stages of data reduction, data presentation, and drawing conclusions based on indicators of depictions of nature and the relationship between humans and nature. The results of the study indicate that the depiction of nature in the book "Stories of Children in a Thousand Rivers" includes natural disasters, environmental pollution, and animal life that are part of the river ecosystem. The relationship between humans and nature is reflected through attitudes of respect for nature, responsibility for nature, and not destroying nature. This relationship demonstrates an ethical relationship between humans and the environment that places humans as part of the natural ecosystem. This study concludes that the book "Stories of Children in a Thousand Rivers" contains ecological educational values ​​that have the potential to shape environmental awareness in child readers.